Perinatal and postpartum care during the COVID‐19 pandemic: A nationwide cohort study. Issue 2 (7th October 2021) - Wagner, Michael; Falcone, Veronica; Neururer, Sabrina B.; Leitner, Hermann; Delmarko, Irmgard; Kiss, Herbert; Berger, Angelika; Farr, Alex
Abstract: Background: This study aimed to analyze perinatal outcomes and adverse events during the COVID‐19 pandemic's first wave to help direct decision making in future waves. Methods: This study was an epidemiological cohort study analyzing comprehensive birth registry data among all 80 obstetric departments in Austria. Out of 469 771 records, 468 348 were considered eligible, whereof those with preterm delivery, birthweight <500 g, multiple fetuses, fetal malformations and chromosomal anomalies, intrauterine fetal death, maternal cancer, HIV infection, and/or inter‐hospital transfers were excluded. Women who delivered between January and June 2020 were then classified as cases, whereas those who delivered between January and June 2015‐2019 were classified as controls. Perinatal outcomes, postpartum hospitalization, and adverse events served as outcome measures. Results: Of 33 198 cases and 188 225 controls, data analysis showed significantly increased rates of labor induction, instrumental delivery, obstetric anesthesia, NICU transfer, and 5‐min Apgar score below 7 during the COVID‐19 period. There was a significantly shorter length of postpartum hospitalization during the COVID‐19 period compared with the non‐COVID‐19 period (3.1 ± 1.4 vs 3.5 ± 1.5 days; P < .001). Significantly more women opted for short‐stay delivery during the COVID‐19 period (3.7% vs 2.4%; P < .001). Those who delivered during the COVID‐19 period were also more likely to experience postpartum adverse events (3.0% vs 2.6%; P < .001), which was confirmed in the logistic regression model (odds ratio, 2.137; 95% confidence interval, 1.805‐2.530; P < .001). Conclusions: Perinatal and postpartum care during the first wave of the COVID‐19 pandemic differed significantly from that provided before. Increased rates of adverse events underline the need to ensure access to high‐quality obstetric care to prevent collateral damage.